Desempeño financiero y mentalidad emprendedora en los artesanos del Mercado Artesanal de Iquitos periodo 2025 - Lam da Costa, Carla Patricia (2025)
The general objective of this research was to evaluate the relationship between financial performance and the entrepreneurial mindset of the artisans of the Iquitos Artisan Market period 2025, with a quantitative approach research type, non-experimental transactional design type and correlational study scope, included as test and sample 51 Artisans from the Iquitos artisan market, it was concluded that there is a moderate and statistically significant positive relationship between financial performance and the entrepreneurial mindset of the artisans of the Iquitos Artisan Market, with Spearman correlation analysis of (ρ = 0.631; p<0.01); in addition, entrepreneurial proactivity shows the strongest relationship with financial performance (ρ = 0.719). Artisans who anticipate, act with initiative, and seek to generate change achieve more effective financial management, confirming that proactivity is a key factor for financial success. Risk tolerance has a moderate positive relationship with financial performance (ρ = 0.550), indicating that artisans willing to take calculated risks tend to achieve higher levels of income and profitability compared to those who prefer a more conservative approach.